2012
DOI: 10.1016/j.vaccine.2012.04.101
|View full text |Cite
|
Sign up to set email alerts
|

Co-administration of morphine and oxycodone vaccines reduces the distribution of 6-monoacetylmorphine and oxycodone to brain in rats

Abstract: Opioid conjugate vaccines have shown promise in animal models as a potential treatment for opioid addiction. Individual vaccines are quite specific and each targets only a limited number of structurally similar opioids. Since opioid users can switch or transition between opioids, we studied a bivalent immunization strategy of combining 2 vaccines that could target several of the most commonly abused opioids; heroin, oxycodone and their active metabolites. Morphine (M) and oxycodone (OXY) haptens were conjugate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(112 citation statements)
references
References 23 publications
6
106
0
Order By: Relevance
“…M-KLH and OXY-KLH produced very high serum antibody concentrations of 0.75 mg/ml, consistent with other reports of heroin and oxycodone vaccine immunogenicity in rats (Anton and Leff, 2006;Pravetoni et al, 2012cPravetoni et al, , 2014aKosten et al, 2013;Raleigh et al, 2013;Jalah et al, 2015), although one report found even higher concentrations of up to 2.8 mg/ml (Stowe et al, 2011). These concentrations are higher than have generally been reported with nicotine or cocaine vaccines using similar linkers and carrier proteins, suggesting that opioid-based haptens are particularly immunogenic, perhaps due to their larger size (Kantak et al, 2000;Keyler et al, 2008;Roiko et al, 2008;Pravetoni et al, 2012a).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…M-KLH and OXY-KLH produced very high serum antibody concentrations of 0.75 mg/ml, consistent with other reports of heroin and oxycodone vaccine immunogenicity in rats (Anton and Leff, 2006;Pravetoni et al, 2012cPravetoni et al, , 2014aKosten et al, 2013;Raleigh et al, 2013;Jalah et al, 2015), although one report found even higher concentrations of up to 2.8 mg/ml (Stowe et al, 2011). These concentrations are higher than have generally been reported with nicotine or cocaine vaccines using similar linkers and carrier proteins, suggesting that opioid-based haptens are particularly immunogenic, perhaps due to their larger size (Kantak et al, 2000;Keyler et al, 2008;Roiko et al, 2008;Pravetoni et al, 2012a).…”
Section: Discussionsupporting
confidence: 90%
“…To measure drug-specific serum IgG antibody titers, morphine or oxycodone haptens conjugated to bovine serum albumin were coated on enzyme-linked immunosorbent assay plates at 5 ng/well in carbonate buffer (pH 9.6) and blocked with 1% gelatin (Pravetoni et al, 2012c;Raleigh et al, 2013Raleigh et al, , 2017. Goat anti-rat IgG conjugated to horseradish peroxidase was used as secondary antibodies (Jackson ImmunoResearch Laboratories, Inc., West Grove, PA).…”
Section: Antibody Characterizationmentioning
confidence: 99%
“…Morphine hapten was synthesized as previously reported (Pravetoni et al, 2012b). Briefly, the C3 position of morphine sulfate was protected with di-tert-butyl carbonate and a tetraglycine (Gly) 4 linker was attached at the C6 to create the hapten M(Gly) 4 (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The total number of moles per kilogram of morphine-specific IgG in rats vaccinated with M-KLH was calculated as the product of the reported IgG volume of distribution (131 ml/kg) in rats and the plasma antibody concentration and converted to moles/kg using a molecular weight of 150 kDa for IgG (Bazin-Redureau et al, 1997;Pravetoni et al, 2012b). The corresponding number of drug-binding sites of IgG was twice that number because there are two binding sites per IgG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation